2009
DOI: 10.1007/s10562-009-0248-9
|View full text |Cite
|
Sign up to set email alerts
|

Diesel-like Hydrocarbons from Catalytic Deoxygenation of Stearic Acid over Supported Pd Nanoparticles on SBA-15 Catalysts

Abstract: Palladium catalysts with different loading on SBA-15 have been prepared using a direct synthesis method and characterized with X-ray diffraction, micrograph images, and X-ray photoelectron spectroscopy. Mesoporous Pd-SBA-15 was an active and selective catalyst for deoxygenation of stearic acid in dodecane as a solvent at 300°C under 17 bar of 5 vol% H 2 in argon as a carrier gas in a semibatch reactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 20 publications
3
49
1
2
Order By: Relevance
“…), SBA-15 has the largest pore, with hexagonally regio-regular arranged mesopores, adjustable pore size, and high thermal stability. 4,16,17 Moreover, SBA-15 was found to be signicantly more effective in deoxygenation than the HMS-supported catalyst.…”
Section: 4mentioning
confidence: 98%
“…), SBA-15 has the largest pore, with hexagonally regio-regular arranged mesopores, adjustable pore size, and high thermal stability. 4,16,17 Moreover, SBA-15 was found to be signicantly more effective in deoxygenation than the HMS-supported catalyst.…”
Section: 4mentioning
confidence: 98%
“…For instance, mesoporous silica nanoparticles have been proven as effective catalyst supports for upgrading microalgae oil using iron nanoparticles (Kandel et al, 2014). Furthermore, stearic acid deoxygenation on Pd/SBA-15 and Pd/C catalysts showed a higher turnover frequency in the case of Pd/SBA-15, indicating the effectiveness of the mesoporous support (Lestari et al, 2010). These materials can also accept new active sites via ion-exchange, adsorption, or grafting techniques (Nava et al, 2009).…”
Section: Role Of Supportmentioning
confidence: 99%
“…71,[74][75][76][77][78][79][80][81][82][83][84] As evidenced by some reports, improvement in Pd-based catalysts in continuous operation may be necessary because some reports suggest they are hindered by rapid deactivation. Maki-Arvela et al 74 reported that the deactivation of a Pd catalyst while decarboxylating lauric acid may have been due to poisoning by the product gases (CO and CO 2 ) and/or coking.…”
Section: Biodieselmentioning
confidence: 99%